Increased short- and long-term mortality amongst patients with early periprosthetic knee joint infection - Olof Thompson; Annette W-Dahl; Anna Stefánsdóttir (BMC Musculoskeletal Disorders, 2022)
Abstract Background Periprosthetic joint infection (PJI) following total knee arthroplasty (TKA) is a severe complication in terms of disability, morbidity, and cost. We performed a study to investigate whether early PJI (within 90 days of primary TKA) is associated with increased mortality. Secondary aims were to compare mortality rates over time and between surgical treatment methods. Methods Patients with suspected PJI were identified by linkage of the Swedish Knee Arthroplasty Register (SKAR) and the Swedish Prescribed Drug Register (SPDR) in 2007–2008 and 2012–2013. Medical records of patients receiving more than 4 weeks of continuous antibiotic therapy were subsequently reviewed to verify the PJI diagnosis. Information on mortality was obtained through the SKAR which is updated daily from the tax agency and patients with PJI were compared to patients without PJI. Results Four hundred sixty-six patients were diagnosed with PJI within 90 days and compared to 40,362 patients without PJI. Mortality rates were significantly higher for PJI patients in both short- and long term: 2.6% vs. 0.8% at 1 year, 4.9% vs. 1.9% at 2 years, 15.7% vs. 7.1% at 5 years, and 38% vs. 21.4% at 10 years. The difference in mortality rate remained after adjusting for sex, age, diagnosis, and time period for surgery with Hazard Ratio 1.8 (95% CI:1.6–2.1). Mortality rates did not differ between time periods, and we found no correlation to surgical treatment. Conclusion Patients with early PJI after primary TKA have an increased mortality rate compared to TKA patients without PJI. Improvements in surgical treatment strategy has not resulted in better survival. Long term difference in mortality rates indicates that PJI is not the sole reason for mortality suggesting a general frailty in PJI patients.